PRINCIPLES OF ORGANIZATION OF METHODICAL WORK IN PRESCHOOL EDUCATIONAL INSTITUTIONS IN MODERN REALITIES - Скрипник, Неля (SWorldJournal, 2022)
The article investigates theoretical frameworks of the organization of methodological work in educational institutions under the conditions of reformation and modernization of the Ukrainian education system.The necessity to re-orient methodological work